2012
DOI: 10.1089/cap.2011.0084
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Antipsychotic Medications to Control Symptoms of Delirium in Children and Adolescents

Abstract: Although randomized placebo-controlled studies are needed, atypical antipsychotic medications appeared to be effective and safe for managing delirium symptoms in pediatric patients while underlying etiology was addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 23 publications
1
56
0
1
Order By: Relevance
“…Over the past decade, there have been increasing reports of delirium in critically ill infants, children, and adolescents (1,(5)(6)(7)(8)(9)(10)(11)(12)(13) as well reports on associated patient outcomes and financial implications (14)(15)(16). Over the past decade, there have been increasing reports of delirium in critically ill infants, children, and adolescents (1,(5)(6)(7)(8)(9)(10)(11)(12)(13) as well reports on associated patient outcomes and financial implications (14)(15)(16).…”
Section: Implementation Of An Icu Bundle: Anmentioning
confidence: 99%
“…Over the past decade, there have been increasing reports of delirium in critically ill infants, children, and adolescents (1,(5)(6)(7)(8)(9)(10)(11)(12)(13) as well reports on associated patient outcomes and financial implications (14)(15)(16). Over the past decade, there have been increasing reports of delirium in critically ill infants, children, and adolescents (1,(5)(6)(7)(8)(9)(10)(11)(12)(13) as well reports on associated patient outcomes and financial implications (14)(15)(16).…”
Section: Implementation Of An Icu Bundle: Anmentioning
confidence: 99%
“…is determined (Turkel 2006). A recent retrospective study on the use of atypical antipsychotics in pediatric delirium (n=110, ages 1–18 years) found that olanzapine, quetiapine and risperidone were tolerated and all reduced symptoms based on the DRS, but efficacy and safety of the antipsychotics were not formally tested (Turkel 2012). …”
Section: Assessment/treatmentmentioning
confidence: 99%
“…Both typical and atypical antipsychotics are used, with predominantly atypical antipsychotic use in children. 16,23,[25][26][27][28] There is limited data for their use in infant in whom congenital abnormalities, laboratory abnormalities, or multiple medications compound the risk for antipsychotic-induced QTc prolongation. Treating infants with these cardiac risk factors is challenging given the potential for arrhythmias with lethal consequences.…”
Section: Discussionmentioning
confidence: 99%